PEMBERIAN PENGHARGAAN YANG EFEKTIF UNTUK MENINGKATKAN MOTIVASI KERJA ROOM BOY/MAID DI INTERCONTINENTAL BALI RESORT - I Gusti Ayu Melistyari Dewi (Jurnal Ilmiah Hospitality Management, 2011)
In general, the products offered by each hotel is the same as the others are multi-product that is a collection of various products such as bedrooms, restaurant, bar, sports facilities, recreation, spa. Like the hotel in general, Intercontinental Bali Resort has several divisions in charge and have different responsibilities to achieve the sole purpose of profit for hotel and guest satisfaction. Inversely with the expectations of consumers, especially from room service division where the high level of guest complaints, this occurs because the room boy / a maid in their duties have been far enough to deviate from the Standard Operating Procedure has been established by the management. As an example, high levels of guest complaints in terms of Guest Room Cleanliness and Cleanliness of bathroom. The main factors that cause the room boy / maid less enterprising, diligent, and not always guided by the SOP, to know it is done interviews on the roomboy. From interviews award system implemented so far by the management of Intercontinental Bali Resort, running less effective It can be shown by the results of interviews conducted by the author, where the high demand from the room boy / maid who choose to promotion, education and training as well as cash as a form of reward they want, note that from forty-five (45) the room boy / maid, a total of eighteen (18) persons or 40% room boy / maid who choose to campaign as one of the desired form of awards to increase their work motivation, whereas the remaining eleven (11) people choose education and training, eight (8) people choose a letter of appreciation and eight (8) more people choose cash